Development of a novel polycaprolactone based composite membrane for periodontal regeneration using spin coating technique. Issue 6 (25th March 2022) - Van, Tran Thi Tuong; Makkar, Preeti; Farwa, Ume; Lee, Byong-Taek
Abstract: Guided bone regeneration (GBR) is known to prevent the development of soft tissue on the defect sites as well as support the new bone formation on the other end. In the present study, we developed a multilayer biodegradable membrane for GBR applications. The multilayer membrane is primarily composed of β-tricalcium phosphate (TCP), polycaprolactone (PCL), and hyaluronic acid (HA), prepared by the spin-coating method. The triple layer system has PCL-TCP composite layer on top, a PCL layer in the middle, and PCL-HA as the bottom layer. The characterization of the PCL-TCP/PCL/PCL-HA by various techniques such as SEM, EDS, XRD, and FT-IR supported the uniform formation of the triple layers with an overall thickness of ∼ 72 µm. Multilayer composite membrane showed excellent physical parameters; neutral pH, high hydrophilicity, high swelling rate, low degradation rate, and high apatite formation after immersion in simulated body fluid (SBF) for 14 days. The multilayer membrane also exhibited biocompatibility which is evident by MTT assay and confocal images. The results suggested that the multilayer composite membrane has the potential for GBR applications.